Media-Education and educational research - Pier Cesare Rivoltella (Universidade Federal de Santa Catarina, 2010)
This text proposes to define the specificity of research in the realm of Media Education in relation to educational research. To do so, it is based on the epistemological framework presented by Van der Maren (2003) contextualizing it in the interior of international research about the relationship between media and education.